2020
DOI: 10.1371/journal.pone.0239444
|View full text |Cite
|
Sign up to set email alerts
|

Speaking up behavior and cognitive bias in hand hygiene: Competences of German-speaking medical students

Abstract: Introduction Infection prevention and speaking up on errors are core qualities of health care providers. Heuristic effects (e.g. overconfidence) may impair behavior in daily routine, while speaking up can be inhibited by hierarchical barriers and medical team factors. Aim of this investigation was to determine, how medical students experience these difficulties for hand hygiene in daily routine. Methods On the base of prior investigations we developed a questionnaire with 5-point Likert ordinal scaled items an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 49 publications
3
20
0
2
Order By: Relevance
“…Next, we could show that in the absence of “horizontal” clinical tribalism (among the professions [ 21 ]), it might be possible that there is a kind of “vertical” clinical tribalism towards students and supervisors. While students may be found easy to be cared for, our data showed that responders seem to not speak up on supervisors in case of witnessing SVP symptoms in them–likely based on hierarchical issues and perhaps anxiety about being blamed for an insulting intervention and fear for stigmatisation or loss of authority [ 22 , 38 , 39 ]. Especially for leaders, it might be relevant that if they face SVP or even develop psychic pathologies, this may affect the safety of patients, staff and the institution’s reputation and economy [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we could show that in the absence of “horizontal” clinical tribalism (among the professions [ 21 ]), it might be possible that there is a kind of “vertical” clinical tribalism towards students and supervisors. While students may be found easy to be cared for, our data showed that responders seem to not speak up on supervisors in case of witnessing SVP symptoms in them–likely based on hierarchical issues and perhaps anxiety about being blamed for an insulting intervention and fear for stigmatisation or loss of authority [ 22 , 38 , 39 ]. Especially for leaders, it might be relevant that if they face SVP or even develop psychic pathologies, this may affect the safety of patients, staff and the institution’s reputation and economy [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…A further effect is the clinical tribalism phenomenon (CTP) belonging to the in-group biases [ 21 ]: comparable to the over-placement-effect: persons estimate their own occupational group to be better than other groups. We were able to demonstrate this related effect for several infection control and communication skills in 2021, summarised in [ 22 ]. Further, our working group generated a hypothesis framework shown in Figure 1 for a better understanding of the different models and their assumed interactions.…”
Section: Introductionmentioning
confidence: 88%
“…Even where whole cohorts were invited to participate, it may be that only those who were motivated to learn participated; it is impossible to know about the relevant motivations of those who did, and did not participate. Heavy reliance was placed on the use of self-reported scales to document practice although student report is a poor indicator of students' hand hygiene performance: over-confidence and tendency to inflate adherence are both well-established (Cole 2009;Bushuven et al 2020). A scale to assess student health workers' knowledge and attitudes to hand hygiene has been developed (Van De Mortel 2009) and validated (Karadag et al 2016) but was adopted by only two research teams and of these, one reported that students encountered difficulties with completion.…”
Section: Discussionmentioning
confidence: 99%
“…Patient safety concerns are common, one study suggesting that 62% of doctors and 80% of nurses reported at least one safety concern in the last four weeks (Schwappach and Richard 2018). However, speaking-up in case of poor hand hygiene may be rare, particularly if there is a hierarchical imbalance (Bushuven et al 2020). The negative impact of hierarchies on voicing safety concerns has been noted more broadly, along with the expected behaviours and socialisation of nurses within the care team (Morrow et al 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation